Case Report: Adolescent-Onset Isolated Nephronophthisis Caused by a Novel Homozygous Inversin Mutation - Zhong, Zhengxia; Yan, Xiaoyong; Fang, Zhengying; Dong, Yijun; Tan, Jiaxing; Xie, Jingyuan; Hu, Linhong; Zhang, Shibin; Qin, Wei (Frontiers in Genetics, 2022)
Objective: Nephronophthisis (NPHP) is a rare autosomal recessive inherited kidney disease that can cause cystic enlargement of the kidneys, and lead to end-stage renal disease (ESRD) before the age of 30 years. Herein we describe a case of adolescent-onset NPHP with a novel homozygous mutation in the inversin gene (INVS). Methods: The patient was a 15-year-old Chinese boy who presented with ESRD. Genetic testing was performed via whole exome sequencing and validated via Sanger sequencing. A novel homozygous INVS mutation was identified (c. 1909C > T; p. Gln637Ter). Results: The results of laboratory examinations included urinary protein 1.05 g/24 h, urine erythrocyte count 5/high-power field, serum creatinine 1,026.2 μmol/L, and estimated glomerular filtration rate 5.8 ml/min/1.73 mm2. Extrarenal features included hypertension and moderate anemia, and his parents were consanguineous (first cousins). A homozygous 1-bp substitution resulting in a nonsense mutation (c. 1909C > T; p. Gln637Ter) in exon 15 of INVS was detected via whole exome sequencing, and validated via Sanger sequencing. According to the classification system of the American College of Medical Genetics and Genomics, the mutated gene in INVS is strongly pathogenic (PVS1+PM2+PP3+PP5). His parents and a younger brother were heterozygous carriers. Based on the above results he was diagnosed with juvenile type 2 NPHP. He underwent hemodialysis, and received a kidney transplant after 2 months. He is currently recovering well, with a serum creatinine level of 117 μmol/L and an estimated glomerular filtration rate of 79.6 ml/min/1.73 mm2. Conclusion: Here we have described an extremely rare case of adolescent-onset type 2 NPHP caused by a homozygous INVS mutation. The patient had progressed to ESRD by the age of 15 years. The current report will deepen our understanding of the clinical and genetic basis of this disease.